Knowledge of obstetrical fistula and its associated factors among reproductive-age women in Ejere Woreda, West Shewa Zone, Oromia Region, Ethiopia: a community-based study - Tiruye, Getahun; Kejela, Daba; Dirar, Anteneh; Goshu, Abel Tibebu; Gultie, Teklemariam (Frontiers in Global Women's Health, 2025)
IntroductionObstetric fistula is a serious and tragic childbirth injury that mainly affects women in resource-limited areas, often leading to social isolation and stigma. While optimal knowledge among women about the prevention, contributing factors, and available treatments for obstetric fistula is crucial for reducing its overall burden, many women in Ethiopia continue to be affected by it and endure its consequences because of a persistent knowledge gap. Therefore, this study aimed to assess the level of knowledge about obstetric fistula and its associated factors among women of reproductive age in Ejere Woreda, West Shewa Zone, Oromia Region, Ethiopia.MethodsA community-based cross-sectional study was conducted among reproductive-age women in Ejere Woreda, West Shewa Zone, Ethiopia, from 1 to 30 June 2024. A systematic random sampling technique was employed to recruit 770 participants. Data were collected using a pretested structured questionnaire, which was then coded and analyzed using SPSS version 27. Variables with a p-value <0.25 in bivariate logistic regression were included in a multivariable logistic regression to identify significant predictors of women's knowledge about obstetric fistula. A p-value <0.05 at a 95% confidence interval (CI) was used to determine statistically significant associations.ResultsThe study found that 46.6% (95% CI: 43.1–50.3) of women had good knowledge about obstetric fistula. Factors significantly associated with the knowledge level of obstetric fistula included being an urban resident [adjusted odds ratio (AOR) = 4.12, 95% CI: 2.36–7.19], access to a TV/radio at home (AOR = 2.51, 95% CI: 1.19–5.25), proximity to health facilities (AOR = 4.88, 95% CI: 2.37–10.04), giving birth at health institutions (AOR = 4.62, 95% CI: 2.56–8.33), attending pregnant women's conferences (AOR = 3.42, 95% CI: 1.88–6.22), and having a history of modern contraceptive use (AOR = 4.82, 95% CI: 2.77–8.37).Conclusion and recommendationsNearly one in two women of childbearing age are knowledgeable about obstetric fistula. The study underscores the need to address the urban–rural disparity in healthcare access and information, enhancing media access, and promoting women's participation in pregnancy conferences to enhance knowledge of obstetric fistula.